Morphology and Electronic Structure of the Oxide Shell on the Surface of Iron Nanoparticles - Wang, Chongmin; Baer, Donald R; Amonette, James E; Engelhard, Mark H; Antony, Jiji; Qiang, You (Journal of the American Chemical Society, 2009)
An iron (Fe) nanoparticle exposed to air at room temperature will be instantly covered by an oxide shell that is typically ∼3 nm thick. The nature of this native oxide shell, in combination with the underlying Fe0 core, determines the physical and chemical behavior of the core−shell nanoparticle. One of the challenges of characterizing core−shell nanoparticles is determining the structure of the oxide shell, that is, whether it is FeO, Fe3O4, γ-Fe2O3, α-Fe2O3, or something else. The results of prior characterization efforts, which have mostly used X-ray diffraction and spectroscopy, electron diffraction, and transmission electron microscopic imaging, have been framed in terms of one of the known Fe−oxide structures, although it is not necessarily true that the thin layer of Fe oxide is a known Fe oxide. In this Article, we probe the structure of the oxide shell on Fe nanoparticles using electron energy loss spectroscopy (EELS) at the oxygen (O) K-edge with a spatial resolution of several nanometers (i.e., less than that of an individual particle). We studied two types of representative particles: small particles that are fully oxidized (no Fe0 core) and larger core−shell particles that possess an Fe core. We found that O K-edge spectra collected for the oxide shell in nanoparticles show distinct differences from those of known Fe oxides. Typically, the prepeak of the spectra collected on both the core−shell and the fully oxidized particles is weaker than that collected on standard Fe3O4. Given the fact that the origin of this prepeak corresponds to the transition of the O 1s electron to the unoccupied state of O 2p hybridized with Fe 3d, a weak pre-edge peak indicates a combination of the following four factors: a higher degree of occupancy of the Fe 3d orbital; a longer Fe−O bond length; a decreased covalency of the Fe−O bond; and a measure of cation vacancies. These results suggest that the coordination configuration in the oxide shell on Fe nanoparticles is defective as compared to that of their bulk counterparts. Implications of these defective structural characteristics on the properties of core−shell structured iron nanoparticles are discussed.